Conformal isoparametric spacelike hypersurfaces in conformal spaces Q^4_1 and Q^5_1 - Bianping, Su; Shu, Shichang (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study the conformal geometry of conformal spacelike hypersurfaces in the conformal spaces Q^4_1 and Q^5_1. We obtain a complete classification of conformal isoparametric spacelike hypersurfaces in Q^4_1 and Q^5_1.